2009
DOI: 10.1177/0163278709356190
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pharmacists in Smoking Cessation in Poland

Abstract: In Poland, 38.0% of men and 25.6% of women smoke daily. One method for expanding access to smoking cessation services is through community-based pharmacists. Surveys were administered in [2007][2008] to (a) current smokers, (b) members of a pharmacy association, and (c) pharmacy students in their final year of training. Pharmacists were the highest ranked health professionals to whom Polish smokers reported they would turn for information about pharmacological support for smoking cessation. Most pharmacists (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Many of the pharmacists (88%) felt it was their duty to provide cessation services, however less than 70% of the pharmacists believed that pharmacists' as a group had the required training to provide either smoking cessation counseling or pharmacotherapy. This is in contrast to findings in Poland where 79% felt they were fully qualified to provide smoking cessation services and provided community based cessation services 42 . Furthermore, an assessment of the factors associated with a willingness to provide smoking cessation services among the respondents was consistent with other studies, 25,43 Respondents who believed that pharmacists' had the required training to provide smoking cessation services were more willing to provide these services.…”
Section: Research Articlecontrasting
confidence: 76%
See 1 more Smart Citation
“…Many of the pharmacists (88%) felt it was their duty to provide cessation services, however less than 70% of the pharmacists believed that pharmacists' as a group had the required training to provide either smoking cessation counseling or pharmacotherapy. This is in contrast to findings in Poland where 79% felt they were fully qualified to provide smoking cessation services and provided community based cessation services 42 . Furthermore, an assessment of the factors associated with a willingness to provide smoking cessation services among the respondents was consistent with other studies, 25,43 Respondents who believed that pharmacists' had the required training to provide smoking cessation services were more willing to provide these services.…”
Section: Research Articlecontrasting
confidence: 76%
“…A similar study among pharmacists in Montana, USA showed similar findings with low rates of inquiry of smoking status of clients. [41] These findings however differ from those reported among pharmacists in Poland where the majority (86%) of the community pharmacists inquired about smoking status and provided both smoking cessation counseling and dispensing of NRT's to their clients 42 .…”
Section: Research Articlementioning
confidence: 70%
“…At present, an involvement of pharmacists in tobacco cessation was encouraged by several organizations including National Health Service (NHS), the International Pharmaceutical Federation (FIP), American Society of Health System Pharmacy (ASHP) (McRobbie and McEwen, 2005, Siiskonen, September 2004, Hudmon and Corelli, 2009). However, barriers of pharmacist to provide smoking cessation counseling are lack of time and lack of knowledge and skill (Goniewicz et al, 2010, El Hajj et al, 2012.…”
Section: Effectiveness Of Tobacco Education For Pharmacy Students In mentioning
confidence: 99%
“…Meanwhile, although Polish patients still connect pharmacists mostly with selling medicaments [ 16 ], there are reports indicating patients’ positive attitudes and expectations for pharmacists’ advice or information on drugs, smoking cessation, and minor or chronic health conditions, including their screening and prevention [ 17 , 18 ]. The majority of Polish pharmacists also express positive attitudes and readiness to expand the scope of their practice [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%